Finite difference solution of radiation effects on MHD unsteady free-convection flow over vertical plate with variable surface temperature - M. A. Abd El-Naby; Elsayed M. E. Elbarbary; Nader Y. Abdelazem (Journal of Applied Mathematics)
An analysis is performed to study radiation effects on magnetohydrodynamic (MHD) unsteady free-convection flow past a semi-infinite vertical plate with variable surface temperature in the presence of transversal uniform magnetic field. The boundary layer equations are transformed into a linear algebraic system by an implicit finite-difference method. A parametric study is performed to illustrate the influence of radiation parameter, magnetic parameter, and Prandtl number on the velocity and temperature profiles. The numerical results reveal that the radiation has significant influences on the velocity and temperature profiles, skin friction, and Nusselt number. The results indicate that the velocity, temperature, and local and average skin friction increase as the radiation parameter increases, while the local and average Nusselt numbers decrease as the radiation parameter increases.